2006
DOI: 10.1890/04-1832
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Change in Benthopelagic Fish Abundance in the Abyssal Northeast Pacific Ocean

Abstract: Abstract. Food web structure, particularly the relative importance of bottom-up and 1 top-down control of animal abundances, is poorly known for the Earth's largest 2 habitats; the abyssal plains. A unique 15-year time-series of climate, productivity, 3 particulate flux, abundance of primary consumers (primarily echinoderms) and 4 secondary consumers (fish) was examined to elucidate the response of trophic levels 5 to temporal variation in one another. Towed camera sled deployments in the abyssal 6 N.E. Pacifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 39 publications
(53 reference statements)
1
46
0
Order By: Relevance
“…Our results are similar to the ecological shifts observed in oceanic ecosystems (Francis et al 1998) and the deep-sea benthos (Wigham et al 2003, Ruhl and Smith 2004, Bailey et al 2006, where climate changes appear to impact ecosystems by causing significant variations in the quantity and quality of food, usually in a bottom-up process. If a longer-term climate trend impacts the sandy bottoms more than, or in addition to, El Viejo, we predict it will still be related to lower plankton productivity caused by warmer water preventing effective delivery of deeper nutrients to the photic zone (Roemmich andMcGowan 1995, McGowan et al 1998).…”
Section: Alternate Hypothesessupporting
confidence: 86%
“…Our results are similar to the ecological shifts observed in oceanic ecosystems (Francis et al 1998) and the deep-sea benthos (Wigham et al 2003, Ruhl and Smith 2004, Bailey et al 2006, where climate changes appear to impact ecosystems by causing significant variations in the quantity and quality of food, usually in a bottom-up process. If a longer-term climate trend impacts the sandy bottoms more than, or in addition to, El Viejo, we predict it will still be related to lower plankton productivity caused by warmer water preventing effective delivery of deeper nutrients to the photic zone (Roemmich andMcGowan 1995, McGowan et al 1998).…”
Section: Alternate Hypothesessupporting
confidence: 86%
“…While useful, such data tell us little about the normal functioning of deep-water communities, provide no information on non-target species and cover only the depths that are commercially fished. When Bailey et al (2006) examined long-term trends in Pacific fishes living in areas deeper than commercial fishing, they discovered that populations varied greatly from year to year. The changes in prey availability, which apparently drove the changes in fish abundance, were probably a result of natural changes in oceanic regime (Ruhl & Smith 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Intuitively, food web studies of abyssal ecosystems often connect the epibenthic megafauna, primarily echinoderms, with top level consumers such as fishes (Smith 1992, Bailey et al 2006. Previous stomach content and isotope analyses have suggested that these 2 macrourid species bypass much of the benthic food web and rely nutritionally upon dead fish and squid sinking from surface waters instead (Drazen et al 2008c).…”
Section: Macrourid Diet Inferred From Fatty Acid Profilesmentioning
confidence: 99%
“…Results from the present study clearly suggest the absence of echinoderms as prey and the importance of carrion, as well as the importance of benthic crustaceans to the macrourids' diet. Bailey et al (2006) suggested that while variation in macrourid abundance covaried with that of echinoderms, it may be other taxa, more important as prey yet not as visible in their camera sled surveys, which are responsible for the population trends observed. Our findings suggest that benthic crustaceans would be the most likely candidate.…”
Section: Macrourid Diet Inferred From Fatty Acid Profilesmentioning
confidence: 99%
See 1 more Smart Citation